ANALISIS PENERAPAN AKUNTANSI AKTIVA TETAP PADA PT MANDALA MULTIFINANCE, TBK. CABANG BERAU - SYAPRUDIN, SYAPRUDIN; RUSTAN, RUSTAN (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2019)
The purpose of this study was to determine the suitability of the application of fixed asset accounting used by PT Mandala Multifinance, Tbk. Berau Branch with the accounting principles contained in the Statement of Financial Accounting Standards (PSAK). To analyze testing the hypothesis used a comparative method, by comparing the treatment of fixed assets according to the company with the treatment of fixed assets according to PSAK No.16. The results show that PT Mandala Multifinance, Tbk. Berau Branch has recorded fixed assets obtained in accordance with the principles of the Statement of Financial Accounting Standards (PSAK) No.16. In terms of depreciation of PT Mandala Multifinance, Tbk. Berau Branch records that for depreciation expenses using the straight-line method, the methods and principles carried out by this company are inaccordance with the Statement of Financial Accounting Standards (PSAK) No.16. Presentation and disclosure of fixed assets in the balance sheet and income statement, in accordance with the treatment of fixed assets according to the Statement of Financial Accounting Standards (PSAK) No.16.